Factores modificables que influyen en el embarazo en adolescentes en el Catón Yaguachi noviembre 2023 - abril 2024. - Secaira Rivera, Luissy Ligner (2024)
Teenage pregnancy is a serious public health problem in the country. The first three causes of hospital discharge for girls and adolescents are due to complications during pregnancy. This is explained by the lack of recognition of girls' rights regarding their sexuality, the patriarchal sexist culture and the influence of ultra-conservative groups in the different spheres of government, which has even influenced the educational program taught in the country. The teen pregnancy rate has been greatly affected recently by several important factors; Therefore, the objective of the research is to determine the modifiable factors that influence pregnancy in adolescents in the Yaguachi canton during the period November 2023 - April 2024. The methodology applied is quantitative, descriptive, and documentary; For this, a sample of 85 pregnant patients from the Yaguachi canton was obtained during the period from November 2023 - April 2024.